Wellbeing measurement among adults with Charcot-Marie-Tooth disease - Payton D. Rule; Megan W. Wolk; Patrick L. Hill (Health Care Transitions)
Background and aims: Wellbeing research among individuals with Charcot-Marie-Tooth disease (CMT) is limited. The goal of the current study is to characterize the challenges experienced by adults with CMT that researchers may miss by utilizing typical strategies to capture mental health and wellbeing. Methods: In 2021, we recruited 288 US adults with CMT (MAge = 60 years, 59% Female, 93% White) to take part in an online survey. Participants were presented with validated wellbeing and health measures, in addition to newly created measures specific to CMT, and then asked to provide free-response feedback about aspects of their lived experiences missing from these measures. Thematic analysis were applied to the free-response data to identify CMT-related difficulties that may impact wellbeing among adults with CMT. Results: Results identified nine CMT-related challenges that are important to individuals with CMT and are often left out of wellbeing assessments in this population. The three most common themes identified were anxiety or worry, coping with loss of function or progression, and difficulty finding knowledgeable medical providers. Further, some aspects of the CMT experience may be comorbid. Interpretation: These results can be used to inform future research and clinical practice in the CMT population.